GAMBARAN SANITASI LINGKUNGAN DI PONDOK PESANTREN AL-HIDAYAH KENALI ASAM BAWAH KOTA JAMBI - Siahaan, Sondang; Fauziah, Rina (NHM PRESS, 2024)
Sanitation in public places, which has the potential for disease transmission, is one of the critical issues in Islamic boarding schools (pondok pesantren). Based on a survey conducted at Pondok Pesantren Al-Hidayah, the environmental sanitation did not meet health standards. Environmental sanitation is a part of environmental health science that includes methods and efforts by individuals or communities to control and manage external environments that are hazardous to health and may threaten human survival. The purpose of this study was to describe the environmental sanitation conditions at Pondok Pesantren Al-Hidayah, Kenali Asam Bawah, Jambi City. This research employed a descriptive method with an observational approach to describe or illustrate phenomena that occurred within the community. The subject of this study was environmental sanitation, which included general conditions, building construction, sanitation facilities, and the requirements for food and beverage management at Pondok Pesantren Al-Hidayah in Kelurahan Kenali Asam Bawah, Jambi City. The results showed that the building construction was categorized as not meeting standards, with a score of 868 or 40%. Sanitation facilities were also categorized as not meeting standards, with a score of 775 or 41.33%. Similarly, the requirements for food and beverage management were categorized as not meeting standards, with a score of 880 or 44.44%.